A Data-Driven Approach to Responder Subgroup Identification after Paired Continuous Theta Burst Stimulation - Heidegger, Tonio; Hansen-Goos, Onno; Batlaeva, Olga; Annak, Onur; Ziemann, Ulf; Lötsch, Jörn (Frontiers in Human Neuroscience, 2017)
Background: Modulation of cortical excitability by transcranial magnetic stimulation (TMS) is used for investigating human brain functions. A common observation is the high variability of long-term depression (LTD)-like changes in human (motor) cortex excitability. This study aimed at analyzing the response subgroup distribution after paired/spaced cTBS as a basis for subject selection. Methods: The effects of paired/spaced cTBS using 80% AMT in 31 healthy volunteers were assessed at the primary motor cortex (M1) corresponding to the representation of the first dorsal interosseous muscle of the left hand, before and up to 50 minutes after plasticity induction. The changes in motor evoked potentials (MEP) were analyzed using machine-learning derived methods implemented as Gaussian mixture modeling and computed ABC analysis. Results: The probability density distribution of the MEP changes from baseline was three-modal, showing a clear separation at 80.9 %. Subjects displaying at least this degree of long-term depression (LTD)-like changes were n = 6 responders. Reassessment using ABC analysis as alternative approach led to the same n = 6 subjects as a distinct category. By contrast, n = 7 subjects displayed a paradox response with increase in MEP. Conclusions: Depressive effects of paired cTBS using 80 % AMT endure at least 50 minutes, however, only in a small subgroup of healthy subjects. Hence, plasticity induction by paired cTBS might not reflect a general mechanism in human motor cortex excitability. A mathematically supported criterion is provided to select responders for enrolment in assessments of human brain functional networks using virtual brain lesions.